The Relationship Between Anxiety and Student Organic Chemistry Learning Achievement at SMK AK Nusa Bangsa Bogor - Oktaviyanti, Nuraini; Irwandi, Dedi; Murniati, Dewi (Universitas Lampung, 2024)
Anxiety has many impacts on human life, one of which is the educational aspect. Anxiety during organic chemistry learning is experienced by students. This is caused by several factors, namely emotional, environmental, and assessment factors. The purpose of this study was to determine the relationship between anxiety and students' organic chemistry learning achievement. The research method used is quantitative method and correlational research model. The sample was taken using purposive sampling, namely 104 12th grade students majoring in Analytical Chemistry class of 2022. Anxiety data was collected through a questionnaire that had been validated by expert lecturers, then Organic Chemistry learning achievement data was obtained from the final assessment of the even semester of Organic Chemistry subjects. The correlation technique used is Product Moment. The results of this study indicate that anxiety has a negative correlation of -0.273 and a significant relationship to learning achievement with a significance value of 0.005. Anxiety and learning achievement have a weak correlation.Keywords: Anxiety, Learning Achievement, Organic Chemistry.DOI: 10.23960/jppk.v13.i3.32318